Ocupação do Movimento Sem Teto: limites, possibilidades e desafios da organização - Suave, Angela Michele (2009)
The current work analyses the organization and support system of an Occupation promoted by the Roofless or Homeless Movement (Movimento Sem Teto) in the city of São José dos Campos, between March 2007 and March 2009. It has as a source of analysis information collected through participant observation of the ethnographic method. It poses a position in the personal trajectories; on the impressions and opinions of people; in the registers on newspapers and in the relations with the religious, political and governmental institutions. It was emphasized the group of elements which support their organization, such as: the living conditions of the occupants, the day-to-day activities of the Occupation and the political-theoretical structure of the organization. The Occupation of Pinheirinho set the debate on the issue of private property and challenged the Public Administration leaders in São José dos Campos. It enabled the organization of social and political powers in a collective manner, reached through the process of demands regarding social rights. It became important for the life of the occupants, especially, to provide for the need of housing. The conscience of class and solidarity built during the Occupation favored the organization of the occupants, for they took their place in the fight of classes and in the history of the city. It allowed the occupants to create a political project with a conscientious direction due to social transformation. Between their limits and possibilities it was left for the Occupation the challenge of organization to extrapolate the fight for social rights and search for human and political emancipation, essentially around the issue of private property